Inflation and Cost of Living in Nepal: A Short- and Long-Term Analysis Using ARDL Modeling - Poudel, Omkar; Kafle, Sarad Chandra; Rijal, Umesh; Acharya, Pradeep (BMC Journal of Scientific Research, 2024)
Inflation significantly affects the cost of living, particularly in developing nations such as Nepal. This research investigates the correlation between inflation and the cost of living, emphasizing crucial economic factors like food prices, exchange rates, and money supply, and employs the Autoregressive Distributed Lag (ARDL) model for analysis. A quantitative methodology is adopted, utilizing secondary data spanning from 1977 to 2023. The study analyzes time series data through unit root tests, ARDL bounds testing, and an Error Correction Model (ECM) to assess both short-term and long-term interactions between inflation and the Consumer Price Index (CPI). Results reveal that food prices, inflation rates, and foreign exchange rates have a significant effect on CPI in both short and long durations. Conversely, money supply and real GDP do not demonstrate significant long-term impacts on inflation. The error correction term indicates a long-term equilibrium relationship among the variables. The research recommends that regulating food prices and exchange rates may help alleviate inflationary pressures in Nepal. It also advises policymakers to prioritize price stabilization initiatives to enhance economic welfare, especially for vulnerable populations. Additionally, the study underscores the necessity of controlling inflation to foster sustainable economic development.